Strategi Guru dalam Mengatasi Kesulitan Belajar Siswa dalam Pembelajaran di Sekolah Dasar - Dhea Divana Anggreni; Ridha Uli Utami Margolang; Nurleli Hasibuan; Santa Grace Naibaho; Tiara Sauna Br Sembiring; Rahmilawati Ritonga (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Learning difficulties are one of the main challenges faced by elementary school students and have a direct influence on the achievement of learning outcomes. These difficulties can come from internal factors, such as low motivation and cognitive abilities, as well as external factors such as a less supportive family environment and less varied learning methods. This article aims to examine the strategies implemented by teachers in overcoming students' learning difficulties based on literature studies. This research uses a literature study method with a qualitative descriptive approach, which utilizes various scientific sources such as journals, books and relevant articles from the last five years. The results of the study show that the strategies used by teachers include providing remedial learning, individual approaches, using varied and fun learning methods and media, providing motivation through rewards, and collaborating with parents to support the learning process at home. Teachers also act as facilitators, motivators and mentors who understand students' characteristics and learning needs. The implications of this research show the importance of increasing teacher capacity and cross-party collaboration to create an adaptive, responsive and inclusive learning environment to support student academic success.